Motional narrowing effects in the excited state spin populations of Mn-doped hybrid perovskites [research data] - Zerhoch, Jonathan; Bodnar, Stanislav; Lerpinière, James E.; Liu, Shangpu; Neumann, Timo; Sergl, Barbara; Heindl, Markus W.; Shcherbakov, Andrii; Elghandour, Ahmed; Klingeler, Rüdiger; Walker, Alison B.; Deschler, Felix (Universität, 2024)
Spin-orbit coupling in the electronic states of solution-processed hybrid metal halide perovskites forms complex spin-textures in the band structures and allows for optical manipulation of excited state spin-polarizations. Here, we report that motional narrowing acts on the photoexcited spin-polarization in CH3NH3PbBr3 thin films, which are doped at percentage-level with Mn2+ ions. Using ultrafast circularly polarized broadband transient absorption spectroscopy at cryogenic temperatures, we investigate the spin population dynamics in our doped hybrid perovskites and find that spin relaxation lifetimes are increased by a factor of three compared to undoped materials. Using quantitative analysis of the photoexcitation cooling processes, we reveal increased carrier scattering rates in the doped perovskites as the fundamental mechanism driving spin-polarization maintaining motional narrowing. Our work reports transition-metal doping of hybrid perovskites as a concept to extend spin lifetimes of hybrid perovskites. (2024-02-19)
Gesehen am 12.03.2024
Gefördert durch: European Research Council: ERC Starting Grant agreement no. 852084 - TWIST
Keywords: Forschungsdaten; Datenbank